2016
DOI: 10.3389/fphar.2016.00079
|View full text |Cite
|
Sign up to set email alerts
|

Activation of α7 Nicotinic Acetylcholine Receptor Decreases On-site Mortality in Crush Syndrome through Insulin Signaling-Na/K-ATPase Pathway

Abstract: On-site mortality in crush syndrome remains high due to lack of effective drugs based on definite diagnosis. Anisodamine (Ani) is widely used in China for treatment of shock, and activation of α7 nicotinic acetylcholine receptor (α7nAChR) mediates such antishock effect. The present work was designed to test whether activation of α7nAChR with Ani decreased mortality in crush syndrome shortly after decompression. Sprague-Dawley rats and C57BL/6 mice with crush syndrome were injected with Ani (20 mg/kg and 28 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…Recent study by Fan et al . reported that administration of Ani contributed to the alleviation of CS in on-site mortality through the α7nAChR-mediated enhancement of insulin sensitivity and the increased phosphorylation of Na/K-ATPase in C2C12 myotubes, which led to the decrease of serum potassium28. We think this could be a mechanism for our observed beneficial effect of Ani/Neo combination on CS in this study.…”
Section: Discussionsupporting
confidence: 56%
“…Recent study by Fan et al . reported that administration of Ani contributed to the alleviation of CS in on-site mortality through the α7nAChR-mediated enhancement of insulin sensitivity and the increased phosphorylation of Na/K-ATPase in C2C12 myotubes, which led to the decrease of serum potassium28. We think this could be a mechanism for our observed beneficial effect of Ani/Neo combination on CS in this study.…”
Section: Discussionsupporting
confidence: 56%
“…PNU‐282987, a potent and selective agonist of α7nAChR (25, 55, 56), has been used to evaluate the effect of these receptors in different models of inflammation (5761). Our results show that PNU‐282987 is efficient for the treatment and prevention of lung inflammation in LPS‐induced ALI in mice, further stressing the importance of the cholinergic anti‐inflammatory pathway and the manipulation of α7nAChR as a pharmacological tool to treat inflammatory diseases (13).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of downregulation of the IR by siRNA on virus production was not as strong as that observed upon Wolbachia infection (Figures 2E and 2F). We then used a selective chemical kinase inhibitor of the IR, hydroxy-2-naphthalenyl-methyl phosphonic acid trisacetoxymethylester (HNMPA(AM)-3) (Fan et al, 2016), to determine whether IR kinase activity is required for ZIKV and DENV replication. Cell toxicity assays revealed that concentrations % 25 mM of the inhibitor are non-toxic for Wolbachia-infected (Aag2wMel) and non-infected (Aag2wMel.tet) cells ( Figure 3A).…”
Section: The Ir Plays An Important Role In Virus Replication In Mosqumentioning
confidence: 99%